Index JCS - JCS Volume 3 (Journal of Consumer Sciences, 2018)
JCS VOL 03 NO 01AIDA 63attitude 3consumption behaviour 3, 4, 5, 10, 11, 13, 14, 49, 50, 51, 53, 56, 58, 60, 63, 65, 70, 76CRI 63electronic money 18, 19, 21, 24, 26, 27, 28, 29, 30, 32functional foods 3intention 18, 19, 21, 24, 27, 28, 30, 32, 34, 47knowledge 3perception 15, 16, 36, 37, 38, 40, 41, 43, 44, 45, 46, 47, 48, 51purchasing behavior 36rural and urban areas 36, 40, 41, 45, 46, 47, 49, 51, 53, 54, 55, 56, 58TPB 1, 18, 24, 32, 34, 35young consumer 3JCS VOL 03 NO 02ACSI 30Ajzen 23attitude toward behavior 17Brand Equity 2Coffee Shop 2consumer independence 44consumer rights awareness 44, 53consumerism 54CSI 59customer loyalty 30customer satisfaction 30Disdukcapil 57E-KTP 57farmer card 17farmers 19Focus Group Discussion 31Generation Y  4healthcare providers 28Independent self-meaning 52information exposure 44, 53inpatients 32insured participants 28intentions 17intervening variables 8IPA 59Lifestyle 2loyal 5marketing 5Marketing Mix 2national health insurance 28Online survey  46outpatients 32perceived behavior control 17PLS 19Purchase Decision 2Quality perception 14satisfaction 28, 57Segmenting, Targeting, and Positioning 13self-construals 44SEM 8, 46service quality 57Servqual 59SERVQUAL 29subjective norms 17theory of planned behavior 18YLKI 45